Consumer Empowerment in Retailing: The Rise of Women Consumers in Retailing (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The growing shopping trend of women customers has offered retailers to ascend to another arrangement of freedoms. The dominant portion of women consumers settles solely on costly goods and administrations. This has helped their faith in decision-making for purchases. Today, in consultation with their male partners, women consumers are known as 'genuine customers.' In decision-making, they are keen, trained and free all over. Relatives, companions and friends respect HER buying choices. She consequently feels more driven and reliable when shopping. Some of the characteristics, such as happiness and enthusiasm, appeared extraordinary from perusing, selecting, eventually dismissing purchasing ('tradingreturning' here and there). As Pierre Martineau puts it aptly, shopping allows a lady to feel like a 'day sovereign'... flattered and imperious. She 286 feels free, independent and active with the opportunity to make choices when shopping. The women of this modern age are highly skilled, used, presented to unfamiliar business sectors, checked and genuinely called for. Subsequently, women customers find themselves on the retailers' radar screen.